Prevalence and aetiological factors of maxillofacial trauma in a rural district hospital in the Eastern Cape - Pillay, Lingeswara (My University, 2017)
Aim: To determine the prevalence, aetiological factors and demographic data of patients presenting with maxillofacial trauma over a six month period at Zithulele Hospital. Materials and Methods: A retrospective, descriptive study was undertaken over a 6 month period (October 2015 – March 2016). All patients who sustained maxillofacial trauma in the study period were recorded. Data collected included demographic data (gender, age), clinical features (pattern of trauma) and the aetiology of the trauma. The radiographic records were sent to a maxillofacial surgeon and a radiologist skilled in maxillofacial interpretation for a diagnosis to be made as well as gaining a second opinion regarding the types of fractures that are seen. Results: A total of 239 patients sustained maxillofacial trauma. The most common aetiological factor was interpersonal violence (55%) followed by road traffic accidents (16%), falls (10%), animals (4%) and other causes (2%). The male to female ratio was 2.6:1 and the 18-24 years age group sustained the most trauma. A total of 210 (88%) patients sustained soft tissue injuries while 29 (12%) sustained hard tissue injuries. Among the soft tissue injuries, 88 sustained lacerations, 16 had hematomas and 84 patients sustained soft tissue injuries that were unspecified. There were 31 fractures diagnosed and the most frequently fractured bone was the mandible at the body. A total of 165 maxillofacial radiographs were assessed, 7% were of no diagnostic value, 56% were of poor diagnostic value and 37% were diagnostically acceptable. Cohen’s Kappa inter-rater reliability test was used to assess the agreement between the two assessors. This demonstrated a Kappa (κ) value of 0.97 (0.81-0.99) which indicates an almost perfect agreement between the assessor. Conclusion: This study showed that maxillofacial trauma is prevalent in rural parts of South Africa. The findings revealed that males aged 18-24 years were more frequently injured as compared to females, with interpersonal violence as a major contributing factor in rural areas.
A research report submitted to the School of Oral Health Sciences, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Dentistry.
Keywords: Maxillofacial Trauma